SISTEM PAKAR DIAGNOSA PENYAKIT AYAM BERBASIS WEB DENGAN METODE CERTAINTY FACTOR - Muhammad Fajar Syadi Muflih; Khaerul Ma’mur (CV. Multi Kreasi Media, 2024)
Mr. Rianto's farm is one of the laying poultry farm in Blitar, at the end of 2021 the farm experienced an outbreak of sudden death which caused losses. In this research, researcher created a web-based expert systems to help farmers diagnose a chicken disease. This system is made using the certainty factor method based on the knowledge of experts/doctors in giving rating weight to each symptom of a disease. In this study, there were 12 types of chicken diseases that could be diagnosed by the system based on the symptoms experienced. Furthermore, programming languages are made using PHP, HTML and MySQL in storing existing data and testing the software using Black Box and White Box testing. This application could help laying hen breeders overcome some of the existing problems such as limited information about chicken diseases. This application could also be used as a tool that could help breeders to maintain livestock production and reduce the risk of sudden death.